Improvements to a Grating-Based Spectral Imaging Microscope and Its Application to Reflectance Analysis of Blue Pen Inks. Issue 8 (August 2015) - McMillan, Leilani C.; Miller, Kathleen P.; Webb, Michael R.
A modified design of a chromatically resolved optical microscope (CROMoscope), a grating-based spectral imaging microscope, is described. By altering the geometry and adding a beam splitter, a twisting aberration that was present in the first version of the CROMoscope has been removed. Wavelength adjustment has been automated to decrease analysis time. Performance of the new design in transmission–absorption spectroscopy has been evaluated and found to be generally similar to the performance of the previous design. Spectral bandpass was found to be dependent on the sizes of apertures, and the smallest measured spectral bandpass was 1.8 nm with 1.0 mm diameter apertures. Wavelength was found to be very linear with the sine of the grating angle (R 2 = 0.9999995), and wavelength repeatability was found to be much better than the spectral bandpass. Reflectance spectral imaging with a CROMoscope is reported for the first time, and this reflectance spectral imaging was applied to blue ink samples on white paper. As a proof of concept, linear discriminant analysis was used to classify the inks by brand. In a leave-one-out cross-validation, 97.6% of samples were correctly classified.